2018
DOI: 10.1002/prep.201800188
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Confinement on the Fracturing Performance of Printed Nanothermites

Abstract: Nanothermites have shown the potential to controllably fracture substrates in applications such as electromechanical systems security. In prior work, both equivalence ratio and material formulation have been varied to tailor fracturing performance. In this paper, material confinement was utilized to further tailor the fracturing performance of aluminum bismuth (III) oxide (Al/Bi2O3) and aluminum copper (II) oxide (Al/CuO) nanothermites. These nanothermites were selectively deposited onto representative substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…One approach for balancing the mechanical integrity, potential energy density, and energy release rate could be to incorporate additives. For example, replacing conventional binders with energetic ones ,− or applying the catalyst embedded with ammonium perchlorate. , Embedding reactive or metal wires is known to promote combustion. New techniques and formulations have been introduced to increase the energetic material content , and control combustion behavior via alterations to the chemical content. , However, since these materials largely rely on nanothermites as their primary energetic component to maximize energy release, it is possible that energy is being inefficiently coupled back into the system to promote propagation, given their longer reaction time . Considering that energy release rates in propellants are determined by how fast reactions occur and how fast energy can be transferred to unreacted material, one could feasibly use thermally conductive materials as a method to improve the heat transfer and energy release rate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach for balancing the mechanical integrity, potential energy density, and energy release rate could be to incorporate additives. For example, replacing conventional binders with energetic ones ,− or applying the catalyst embedded with ammonium perchlorate. , Embedding reactive or metal wires is known to promote combustion. New techniques and formulations have been introduced to increase the energetic material content , and control combustion behavior via alterations to the chemical content. , However, since these materials largely rely on nanothermites as their primary energetic component to maximize energy release, it is possible that energy is being inefficiently coupled back into the system to promote propagation, given their longer reaction time . Considering that energy release rates in propellants are determined by how fast reactions occur and how fast energy can be transferred to unreacted material, one could feasibly use thermally conductive materials as a method to improve the heat transfer and energy release rate .…”
Section: Introductionmentioning
confidence: 99%
“…40−42 New techniques and formulations have been introduced to increase the energetic material content 29,43 and control combustion behavior via alterations to the chemical content. 44,45 However, since these materials largely rely on nanothermites as their primary energetic component to maximize energy release, it is possible that energy is being inefficiently coupled back into the system to promote propagation, given their longer reaction time. 46 Considering that energy release rates in propellants are determined by how fast reactions occur and how fast energy can be transferred to unreacted material, one could feasibly use thermally con- ductive materials as a method to improve the heat transfer and energy release rate.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown that nanothermite is suitable for use in small‐scale igniters [17]. Al‐Bi 2 O 3 nanothermite was chosen as a candidate for testing the conductive polymer igniter‘s ability to ignite energetic material due to its destructive capabilities and ease of fabrication, as demonstrated in prior work [18]. The Al‐Bi 2 O 3 nanothermite was deposited on top of eight spark gap igniters using a BioFluidix PipeJet P9 system with a 500 μm nozzle.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This observation proves the irreversible and extensive damage of the MEMS chip. Note, however, that nanothermites are damaged not only by high temperature but also by fracturing via shock wave [200,201], which is analogous to the action of deposited explosives [185]. Another application patented by Ellis discloses the heat-up production of lithographic printing plates, photomasks, and proofing sheets by an intermetallic reactive layer [202].…”
Section: Localized Heat Sources (Destructible Materials Joining Thementioning
confidence: 99%